The genus Ranatra Fabricius (Heteroptera: Nepidae) in Borneo, with a redescription of Ranatra spinifrons Montandon and the description of a new species - Tran, A.d.; Poggi, R. (Zootaxa, 2019)
The type of Ranatra spinifrons Montandon, 1910 is redescribed and this taxon is reported from Brunei for the first time. Ranatra heoki sp.n. is described from Sarawak and belongs to the Ranatra gracilis group (sensu Lansbury, 1972). The present paper also provides the first records of the following species for Borneo: Ranatra parmata Mayr, 1865 (from Sabah and Kalimantan); Ranatra rafflesi Tran & Polhemus, 2012 (from Sarawak). The latter is also reported from Sumatra for the first time. Ranatra longipes longipes Stål, 1861, previously known from Kalimantan and Sabah, is now reported from Sarawak for the first time. Thus, six species of Ranatra are currently known from Borneo.